Correction: Exploring the photoexcited electron transfer dynamics in artificial sunscreen PBSA-coupled biocompatible ZnO quantum dots. (16th June 2022) - Mubeen, Muhammad; Khalid, Muhammad Adnan; Shahrum, Saba; Mukhtar, Maria; Sumreen, Poshmal; Tabassum, Mamoona; Ul-Hamid, Anwar; Nadeem, Muhammad Arif; Iqbal, Azhar
Abstract : Correction for 'Exploring the photoexcited electron transfer dynamics in artificial sunscreen PBSA-coupled biocompatible ZnO quantum dots' by Muhammad Mubeen et al., New J. Chem., 2022, 46, 9526–9533, ; https://doi.org/10.1039/D2NJ01153K .